THE USE OF READER’S DIGEST MAGAZINE IN READING COMPREHENSION - Diah Eka Marsanti; Ch Evy Tri. W. (English Education Department Slamet Riyadi University Surakarta, 2019)
This research aimed to improve students’ reading comprehension using media reder’s digest magazine at SMPN 7 Surakarta class VIII C. This method was Classroom Action Research. In this study, there were two cycles and ended by post tests. In each cycle there were four procedures, plan, act, observe and reflect. In collecting the data it,consists of tests and non-tests.The results of the implementation of Reader’s Digest Magazine could be shown by the mean score of pre test, post test 1 and post test 2. The mean score of pre test was 56.42, in post test 1 was 78.03. and post test 2 was 81.29. In the use of Reader’s Digest Magazine has made the students felt happy, active, relaxed, more confident, and increases students' learning motivation in the teaching and learning process. Key Word: Classroom Action Research, Reading Comprehension, Reader’s Digest Magazine.